Synthesis and Investigation of Macromolecular Photoswitches - Pang, Juan; Kong, Jingyang; Xu, Jialing; Mao, Xincheng; Hu, Xiaohong (Frontiers in Materials, 2020)
The photoisomerization of azobenzene (AZO) makes it a potential type of photoswitch for the field of chemical engineering. However, the lack of stability and photobleaching characteristics of reversible photoisomerization have restricted further application of AZO as a photoswitch. Therefore, we have designed two polymers containing the AZO domain as macromolecular photoswitches and investigated their switching performance. The hydrophilic monomers hydroxyethyl methylacrylate (HEMA) and N-vinyl-2-pyrrolidone (NVP) were chosen to copolymerize with the AZO monomer to form HEMA-AZO copolymer and HEMA-NVP-AZO terpolymer. The domain content was calculated by integration of the peaks in the 1H NMR spectrum. Real-time UV spectra of polymer solutions upon UV light irradiation confirmed quick and successful trans-to-cis transition for the AZO domain. In reverse, the operable and controllable recovery processes upon white light were also verified by real-time UV spectra. Furthermore, repeated irradiation by UV light and white light for 20 times was used to check their fatigue resistance and recyclability. Importantly, recovery behaviors for the two polymers could be adjusted by solvent property, environment temperature, and light intensity. Higher environment temperature or higher light intensity resulted in shortened recovery time. The influence of solvent was only slightly different for the two polymers. Nanoassemblies, which were formed by HEMA-NVP-AZO terpolymer and poly(β-cyclodextrin)/poly(α-cyclodextrin), exhibited similar controllable switching performance to the pure polymer. In brief, the effectiveness and efficiency of the polymers as photoswitches have been confirmed by results in this work.